2012
DOI: 10.1155/2012/649640
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Marker of the Cisplatin-DNA Interaction: X-Ray Photoelectron Spectroscopy of CL

Abstract: The development of cisplatin and Pt-based analogues anticancer agents requires knowledge concerning the molecular mechanisms of interaction between such drugs with DNA. However, the binding dynamics and kinetics of cisplatin reactions with DNA determined by traditional approaches are far from satisfactory. In this study, a typical 20-base oligonucleotide (CGTGACAGTTATTGCAGGCG), as a simplified model representing DNA, was mixed with cisplatin in different molar ratios and incubation time. High-resolution XPS sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…In this manner, the relative amount of each element can be estimated within the probing depth. The XPS characterization of these bonds for DNA and cisplatin–DNA complexes have been reported previously . The same assignments relating to the four principal elements apply to the present study.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…In this manner, the relative amount of each element can be estimated within the probing depth. The XPS characterization of these bonds for DNA and cisplatin–DNA complexes have been reported previously . The same assignments relating to the four principal elements apply to the present study.…”
Section: Resultssupporting
confidence: 71%
“…It has been shown that the introduction of cisplatin generally induces substantial positive BE shifts of DNA elements compared to that of pure DNA. 30 Consistently, before irradiation for N 1s, the amino and imino species of cisplatin−DNA complexes shift to higher BE of 0.5 ± 0.1 and 0.7 ± 0.1 eV, respectively, compared to that of DNA. Figure 3c illustrates that C−OH (O-1) and carbonyl group (O-2) show positive BE shifts of 0.4 ± 0.1 and 0.9 ± 0.1 eV with the addition of cisplatin, while the O-3 exhibits no substantial BE shift.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…The precise binding energy locations were identified by deconvolution of the experimental curve at 197.4 and 198.3 eV, respectively. The presence of sharp bands in the high-resolution spectra at Cl 2p 1/2 is attributed to chloride ion from solubilized cisplatin in water . Overall, it appears that the RESS-processed cisplatin seemed to (mostly) retain its chemical and structural identity.…”
Section: Resultsmentioning
confidence: 89%
“…The presence of sharp bands in the high-resolution spectra at Cl 2p 1/2 is attributed to chloride ion from solubilized cisplatin in water. 37 Overall, it appears that the RESS-processed cisplatin seemed to (mostly) retain its chemical and structural identity. In principle, these characterizations are expected to serve as a benchmark for our future cisplatin optimization studies.…”
Section: ■ Resultsmentioning
confidence: 96%